BIARLAH ORANG MATI MENGUBURKAN ORANG MATI Investigasi Latar Kultural Matius 8:21-22/Lukas 9:59-60 - Deky Hidnas Yan Nggadas (Sekolah Tinggi Teologi Moriah, 2019)
The text of Matthew 8:18-22 and its parallel in Luke 9:57-59 contain a deep meaning and also requires exegetical attention to find the meaning. The reason to finding meaning in the texts was due to differences of opinion about the background, such as the cultural aspect behind disciple’s reason for “going to bury my father first” and the purpose of Jesus’s response: “let the dead buried their people”. The context is closely related to Jewish burial tradition (known as liqut ‘azamot or ossilegium). However, on the other hand, responsibility to caring parent who died was part of the fifth commandment in Dekalog: “Respect your father and mother.” Teks Matius 8:18-22 dan paralelnya yakni Lukas 9:57-59 mengandung makna yang mendalam dan membutuhkan perhatian eksegetis untuk mendapatkan makna tersebut. Alasan mendapatkan makna pada teks-teks tersebut disebabkan adanya perbedaan pendapat mengenai latar belakangnya, termasuk aspek kultural di balik alasan sang murid untuk “pergi dahulu menguburkan ayahku” dan maksud dari respons Yesus, “biarlah orang mati menguburkan orang-orang mati mereka”. Konteks tersebut terkait erat dengan tradisi penguburan dalam lingkungan Yahudi (disebut dengan liqut ‘azamot atau ossilegium). Namun, di sisi lain, tanggung jawab mengurus orang tua yang meninggal merupakan bagian dari perintah kelima dalam Dekalog: “Hormatilah ayahmu dan ibumu.”